CdS/MoS2 Nanoparticles on Nanoribbon Heterostructures with Boosted Photocatalytic H2 Evolution under Visible‐light Irradiation. Issue 10 (9th March 2021) - Ma, Di; Lu, Qifang; Guo, Enyan; Tao, Furong; Wei, Mingzhi
Abstract: The construction of the heterostructures with intimate contacts and prominent sunlight absorption capacity are essential for achieving the highly effective photocatalytic H2 evolution. Here, the CdS/MoS2 heterostructures constituted by CdS nanoparticals loaded on uniform MoS2 nanoribbons were synthesized through solid‐gas reaction and hydrothermal treatments. In the as‐prepared CdS/MoS2 heterostructures, there are large‐area contact interfaces between the external highly dispersed small CdS nanoparticals and MoS2 nanoribbons. Impressively, the optimized CdS/MoS2 ‐8 photocatalyst delivered the highest hydrogen production rate of 91.2 μmol h −1, which is 9 times that of CdS. It demonstrates that the formation of the heterostructures could eﬀectively promote the separation and transfer of photogenerated charge carriers due to the intimate contacts between CdS nanoparticals and MoS2 nanoribbons. This work would provide a new method to develop efficient photocatalysts for photocatalytic H2 evolution. Abstract : The special structure of CdS nanoparticles dispersed on MoS2 nanoribbon heterostructures possess the excellent photocatalytic H2 evolution performance. It reveals that MoS2 nanoribbons acts as a co‐catalyst can promote the transfer and reduce the recombination of photogenerate charge carriers.